Palladium-catalyzed cascade carbonylative annulation between alkene-tethered aryl iodides and carbon monoxide - Zhang, Yong; Sun, Ya-Kui; Chang, Ya-Ping; Shao, Hui; Zhao, Yu-Ming (Chemical communications (Cambridge, England), 2021)
Rapid construction of molecules bearing all-substituted quaternary stereocenters represents a highly significant but challenging task in organic synthesis. Herein, we report a novel palladium-catalyzed cascade between alkene-tethered aryl iodides and carbon monoxide, which has resulted in a practical and powerful method for the synthesis of complex polycyclic molecules containing aryl-substituted quaternary stereocenters. Mechanistic studies suggested that the reaction proceeded via a Heck-type carbonylative cyclization, followed by a ketene-involved Friedel-Crafts acylation. A novel Pd-catalyzed carbonylative cascade of alkene-tethered aryl iodides has been developed. Mechanistic studies suggested the reaction proceeded via a Heck-type carbonylative cyclization, followed by a ketene-involved Friedel-Crafts acylation.